2021
DOI: 10.3389/fcell.2021.736603
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 Alleviates Cardiomyocyte Apoptosis by Improving Fatty Acid Oxidation in Mitochondria

Abstract: Sepsis-induced cardiac injury (SIC) is one of the most common complications in the intensive care unit (ICU) with high morbidity and mortality. Mitochondrial dysfunction is one of the main reasons for SIC, and Interleukin-13 (IL-13) is a master regulator of mitochondria biogenesis. The aim of the present study was to investigate the role of IL-13 in SIC and explore the underlying mechanism. It was found that reactive oxygen species (ROS) production and apoptosis were significantly increased in lipopolysacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The disorder of lipid metabolism increases reactive oxygen species (ROS) production and fission of mitochondrial, leading to mitochondrial dysfunction and cell apoptosis ( 7 9 ). Recent studies have revealed the disorder of lipid metabolism in several kinds of sepsis-induced organ injury ( 10 , 11 ), which has also been observed in septic myocardial tissue in our previous work ( 12 ), however, via unclear mechanisms.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…The disorder of lipid metabolism increases reactive oxygen species (ROS) production and fission of mitochondrial, leading to mitochondrial dysfunction and cell apoptosis ( 7 9 ). Recent studies have revealed the disorder of lipid metabolism in several kinds of sepsis-induced organ injury ( 10 , 11 ), which has also been observed in septic myocardial tissue in our previous work ( 12 ), however, via unclear mechanisms.…”
Section: Introductionmentioning
confidence: 57%
“…The cellular model of SIC was established by lipopolysaccharide (LPS, Sigma-Aldrich, United States) incubation based on reported protocol ( 12 , 24 ). Briefly, H9C2 cells were cultured in DMEM containing 10 μg/ml LPS for 12 h. Morphology of cardiomyocytes was observed.…”
Section: Methodsmentioning
confidence: 99%
“… 43 , 44 Inhibition of FAO instigates metabolic reprogramming, disturbing the equilibrium in substrate utilization and leading to the accumulation of excess TGs in the myocardium. 10 , 45 This also inhibits mitochondrial function, 12 fosters apoptosis, 46 induces cellular stress, and contributes to the occurrence of arrhythmias, 47 ultimately exacerbating myocardial injury 48 as a phenomenon known as cardiac lipotoxicity. Supporting our data, UA reduces TG accumulation and restores this mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that IL13 is associated with mitochondrial dysfunction in patients with sialadenitis [ 14 ] and protects the mitochondria of cardiomyocytes in patients with septicemia [ 13 ]. Increased IL13 expression has been reported in the dysfunctional mitochondria of mice with house dust mite-induced asthma [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL13 frequently accompanies mitochondria-related conditions, including in infectious disease [ 13 ], inflammatory diseases [ 14 ], and metabolic diseases [ 15 ] and even in cancers [ 16 ]. IL13 has also been reported to be associated with mitochondrial dysfunction in an animal-induced asthma model [ 17 ].…”
Section: Introductionmentioning
confidence: 99%